Improvement of the photochromism taking place on ZnO/MoO3 combined material interfaces. Issue 2 (11th January 2021) - Andron, Ines; Marichez, Léa; Jubera, Véronique; Fargues, Alexandre; Frayret, Christine; Gaudon, Manuel
Abstract : MoO3 /ZnO mixtures obtained using polyol synthesis exhibit an enhanced photochromism. Abstract : Recently, we discovered a huge photochromic effect for ZnO/MoO3 powder mixtures compared with the corresponding single oxides. The former study focused on the coloring efficiency after UV-light irradiation and demonstrated that the pre-existing electrons in the conductive band of ZnO are of huge importance to the photochromism efficiency. Herein, the creation of the "self-closed Schottky barrier" at the solid–solid interfaces between the two oxides, associated with the full redox reaction at the origin of the photochromic properties, was modulated by (i) doping ZnO with Al 3+ ions, (ii) annealing the powder mixture under low p(O2 ) atmosphere, and (iii) synthesizing our own ZnO nanoparticles and MoO3 particles using a polyol process. The characterization of the colouring effect under irradiation as well as the self-bleaching process allowed shedding light on this very complex photochromic mechanism. The coloring and bleaching efficiency ( i.e. possibility to darken to more or less deep blue and to come back to the virgin material optical properties without any deterioration) depends upon multiple interconnected parameters controlling either the particle size and the interface areas between MoO3 and ZnO oxides or the number of pre-electrons in conduction bands of ZnO and MoO3 oxides. By correctly interpreting the ins and outs of the photochromism taking place at the created Schottky barriers in these binary ZnO/MoO3 mixtures, the exchange of the electrons and the oxygen anions through this Schottky interface can be manipulated in order to optimize the huge photochromism phenomenon.